Synthesis, Characterization, and Biological Activity of N′-[(Z)-(3-Methyl-5-oxo-1-phenyl-1,5-dihydro-4H-pyrazol-4-ylidene)(phenyl)methyl]benzohydrazide and Its Co(II), Ni(II), and Cu(II) Complexes - Jonnie N. Asegbeloyin; Oguejiofo T. Ujam; Emmanuel C. Okafor; Ilknur Babahan; Esin Poyrazoglu Coban; Ali Özmen; Halil Biyik (Bioinorganic Chemistry and Applications)
Reaction of 1-phenyl-3-methyl-4-benzoyl-pyrazol-5-one and benzoyl hydrazide in refluxing ethanol gave N′-[(Z)-(3-methyl-5-oxo-1-phenyl-1,5-dihydro-4H-pyrazol-4-ylidene)(phenyl)methyl]benzohydrazide (HL1), which was characterized by NMR spectroscopy and single-crystal X-ray structure study. X-ray diffraction analyses of the crystals revealed a nonplanar molecule, existing in the keto-amine form, with intermolecular hydrogen bonding forming a seven-membered ring system. The reaction of HL1 with Co(II), Ni(II), and Cu(II) halides gave the corresponding complexes, which were characterized by elemental analysis, molar conductance, magnetic measurements, and infrared and electronic spectral studies. The compounds were screened for their in vitro cytotoxic activity against HL-60 human promyelocytic leukemia cells and antimicrobial activity against some bacteria and yeasts. Results showed that the compounds are potent against HL-60 cells with the IC50 value ≤5 μM, while some of the compounds were active against few studied Gram-positive bacteria.